Reviving tourism post Covid-19 Pandemic - Reviving tourism post Covid-19 Pandemic (Kurukshetra: A Journal on Rural Development)
While the pandemic had a visibly negative impact on tourism, it has opened the passivity for niche tourism related to Ayush and wellness. - Reproduced